Investigation on structural and optical properties of porous SnO2 nanomaterial fabricated by direct liquid injection chemical vapour deposition technique. (1st June 2022) - Verma, Arpit; Kumar, Utkarsh; Chaudhary, Priyanka; Yadav, B.C.
Abstract: In the present study, Cassiterite SnO2 thin film synthesized by direct liquid injection chemical vapour deposition method. The surface morphology of the nanomaterial exhibited the rope-like structures with nanospheroid. Peak broadening in the prepared material is analyzed by Scherrer, modified Scherrer, Williamson-Hall, Size-strain and Halder-Wagner methods for investigation of crystallite size and intrinsic strain. The optical properties of the nanomaterial such as bandgap (Eg ), absorption coefficient (α), skin depth (δ), optical density (Dopt ), extinction coefficient (k), refractive index (n), and dielectric constants (εi and εr ) are analyzed by using the UV–Visible transmittance and reflectance spectrum of the prepared SnO2 nanomaterial. The optical band gap of SnO2 based thin film was calculated by the Tauc plot and found to be 3.8 eV. Highlights: Cassiterite SnO2 thin film synthesized by direct liquid injection CVD method. The surface morphology of the nanomaterial exhibited the rope-like structures with nanospheroid. The structural investigation has been done with several parameters, Williamson-Hall, Size-strain and Halder-Wagner methods for investigation of crystallite size and intrinsic strain. The optical properties of the nanomaterial such as optical density (Dopt ), extinction coefficient (k), refractive index (n), and dielectric constants (εi and εr ) are analyzed.